Labor markets and poverty in village Economies - Bandiera, Oriana; Burgess, Robin; Das, Narayan Chandra; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (Oxford Academic, 2022)
This article was published in The Quarterly Journal of Economics [© The Author(s) 2017. Published by Oxford University Press, on behalf of the President and Fellows of Harvard College] and the definite version is available at: https://doi.org/10.1093/qje/qjx003 The Article's website is at: https://academic.oup.com/qje/article-abstract/132/2/811/3075123?redirectedFrom=fulltext